Human-AI Heuristic Evaluation: Uncovering usability insights of an LLM Chatbot Interface for Personalized Learning in Autism - Zaidan, Yuri P. S.; Monteiro, Eric F.; Ruiz, Duncan; Sales, Afonso; Silveira, Milene (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
The rise of Large Language Models (LLMs) and Generative AI (GenAI) offers new possibilities for personalized learning but also introduces usability challenges, especially in applications designed to customize the learning experience for individuals with autism spectrum disorder (ASD). To analyze whether an LLM-powered chatbot interface is effective for this specific use case, we propose a usability heuristics inspection carried out by both human experts and an AI agent to evaluate an LLM interface for ASD curriculum personalization. Preliminary results reveal human and AI-driven usability insights towards a frictionless experience for GenAI educational interventions.